Human Resource Practices Influencing Employees Productivity in the Department of National Registration Bureau Nairobi County, Kenya - Kyenzi, Eunice Kaluki; Kinyili, Jacinta; Nzioki, Susan (THE INTERNATIONAL JOURNAL OF BUSINESS & MANAGEMENT, 2020)
The main purpose of this research work was to find out the human resource practices that influence employees’ productivity in the department of national registration bureau Nairobi county. National Registration Bureau department (NRB) is one of the key department keys in the Ministry of Interior and Coordination of National Government in the Office of President. It operates under the state department of interior. It is mandated to perform activities relating to the registration of persons in line with the Constitution of Kenya. The study made use descriptive research design to collect primary data from the respondents using closed and opened ended questionnaires. This study had a target population of eight hundred (800) officers comprising of middle level managers, technical officers and support staff. It made use of stratified and systematic random sampling. The data was collected and analyzed by use of descriptive statistics e.g. frequencies and percentages Using Statistical Package for Social Sciences (SPSS) alongside inferential statistics where regression model is applied. The findings were that the Staff Training in National Registration Bureau Department helps in determining of training needs, performance appraisal helps in giving feedback on their work and in justifying pay increases, compensation according to the NRB department is the benefits that employees receive in exchange for the service they provide to the department. The study recommends that Training should be the teaching, or developing in oneself or others, any skills and knowledge that relate to specific useful competencies. Training should have specific goals of improving one's capability, capacity, productivity and performance.
Keywords: Human resource Management practices (HRMP), Employee productivity